Unravelling the Digestibility and Structure–Function Relationship of Lentil Protein Through Germination and Molecular Weight Fractionation - Armin Mirzapour-Kouhdasht; Samaneh Shaghaghian; Marjan Majdinasab; Jen-Yi Huang; Marco Garcia-Vaquero (Foods)
This study explores for the first time the impact of a 6-day germination process on the structure (FTIR), antioxidant activity, nutritional/safety attributes (ACE-I inhibitory activity, digestibility, and cytotoxicity), and functional properties of fractions of variable molecular weight (W > 5 kDa; 3 kDa < MW < 5 kDa; and MW < 3 kDa) isolated from proteins extracted from lentils. FTIR results indicated a substantial increase in β-sheet contents during germination. The digestibility of proteins increased from day 0 (16.32–17.04%) to day 6 of germination (24.92–26.05%) with variable levels of digestibility depending on their MW. ACE-I inhibitory activity improved during germination in all fractions, reaching IC50 values of 0.95, 0.83, and 0.69 mg/mL after 6 days of germination. All antioxidant activities analyzed notably increased, particularly in low-MW fractions (MW < 3 kDa). The functional properties of low-MW fractions were also the most promising, displaying the highest water and fat binding capacities and emulsifying and foaming capacities but lower foaming and emulsifying stability compared to high-MW fractions. Cytotoxicity tests on L929 cells revealed the slight adverse effects of low-MW fractions during germination. This study provides insights into the enhanced nutritional and functional attributes of lentil proteins following germination, emphasizing their potential application in functional foods.